Source code and data for the PhD thesis "Measuring the contributions of vision and text modalities in multimodal transformers" - Pârcălăbescu, Letiția (Universität, 2024)
This dataset contains source code and data used in the PhD thesis "Measuring the Contributions of Vision and Text Modalities in Multimodal Transformers". The dataset is split into five repositories: Code and resources related to chapter 2 of the thesis (Section 2.2., method described in "Using Scene Graph Representations and Knowledge Bases"). Code and resources related to chapter 3 of the thesis (VALSE dataset). Code and resources related to chapter 4 of the thesis: MM-SHAP measure and experiments code. Code and resources related to chapter 5 of the thesis: CCSHAP measure and experiments code related to large language models (LLMs). Code and resources related to the experiments with vision and language model decoders from chapters 3, 4, and 5.